2007
DOI: 10.1002/ccd.20980
|View full text |Cite
|
Sign up to set email alerts
|

Diabetes mellitus does not preclude stabilization or improvement of renal function after stent revascularization in patients with kidney insufficiency and renal artery stenosis

Abstract: Renal artery stent placement appears to be equally beneficial in preserving renal function in DM and NDM patients with ischemic nephropathy and global renal ischemia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
5
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 27 publications
1
5
0
Order By: Relevance
“…The current literature contains conflicting reports on the role and efficacy of stent placement for the therapy of RAS in-patient with diabetes mellitus. [38, 40, 41]. The findings in this study are consistent with those that were observed in ASTRAL and CORAL.…”
Section: Discussionsupporting
confidence: 91%
“…The current literature contains conflicting reports on the role and efficacy of stent placement for the therapy of RAS in-patient with diabetes mellitus. [38, 40, 41]. The findings in this study are consistent with those that were observed in ASTRAL and CORAL.…”
Section: Discussionsupporting
confidence: 91%
“…43 In contrast, there have been several studies reporting the majority of patients to either have a stabilization or improvement of sCr after RASt. [14][15][16][17][18][19][20][21][23][24][25][26][27][28][29] The major concern is the proportion of patients with worsening renal function after RASt. An obvious concern during RASt is the potential of embolization secondary to interaction with the plaque during the intervention.…”
Section: Discussionmentioning
confidence: 99%
“…12 There is compelling observational data that RASt stabilizes or improves renal function for patients with ARAS. [14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29] The objective of our study was to identify predictors of renal function outcome after RASt, and to assess overall changes in renal function after RASt.…”
mentioning
confidence: 99%
“…[1][2][3][4] Balloon-expandable stents are primarily utilized to treat ostial lesions, while angioplasty alone has been advocated for more distal lesions. 5 Recently, pure endovascular treatment of juxtarenal and thoracoabdominal aneurysms has been described.…”
mentioning
confidence: 99%